Pengaruh Sistem Informasi Akuntansi Dan Sistem Pengendalian Manajemen Terhadap Kinerja Pegawai - Lubis, Sri Mulyani; Ayu, Sandra; Hendra, Wel (Disclosure: Journal of Accounting and Finance, 2022)
Employee performance can be achieved if the company properly implements an accounting information system and management control system. This study aimed to determine the effect of accounting information systems and management control systems on the performance of the Kotanopan sub-district employees. This research is a type of quantitative research with primary data sources obtained by distributing questionnaires to 30 employees. Multiple linear regression was used to analyze the data. The results showed that the accounting information system had no significant effect on the performance of the Kotanopan sub-district employees and the management control system significantly affected the performance of the Kotanopan sub-district employees. This means that the better the management control system in the company, organization, or agency, the more employee performance will also increase.